Reliable thin chip peeling from adhesive tape with inverted needle ejecting and spring buffering. Issue 7 (3rd April 2018) - Hong, Jinhua; Chen, Jiankui; Xu, Zhoulong; Yin, Zhouping
Abstract: Nondestructively and efficiently peeling thin chip from the adhesive tape is still one of the crucial techniques in IC packaging technology. In order to improve the process efficiency, a novel approach with the inverted ejecting mechanism and spring buffer head is proposed, where, however, the ejecting and spring forces applied at the chip for generating the interfacial crack are also more likely to resulting in the damage of chip. In view of this, an effective theoretical and finite element models are established considering the tape–adhesive–chip structure with ejecting and spring forces, and in the frame of fracture mechanics, the energy release rate is calculated and introduced to reveal effects of the spring buffer on the interfacial crack growth and chip breaking stresses. It is showed that the spring buffer is able to reduce the stress concentration on chip. Furthermore, according to the competing fracture behavior between the interfacial delamination and the chip cracking, the process window of thin chip peeling is suggested for selecting an appropriate spring coefficient and ejecting needle force.